The orientation of learning Mandarin among second year students of Mandarin study program - Ventivani, Aiga; Ling, Ting Hie (Universitas Negeri Malang, 2023)
The curriculum at the Chinese Language Study Program Malang State University is periodically reviewed once every year. The Chinese Language Study Program curriculum at Malang State University has been structured based on a Life-based Learning Curriculum. The preparation of this catalog has been attempted based on the conditions and developments at the time this catalog was published. It is intended that the curriculum used continues to develop for the better and in accordance with the needs from time to time. Curriculum improvements continue to be made in addition to adjusting needs as well so that students are able to compete and face the world of work. Therefore, the curriculum presented must keep up with the times, but not be carried away by the changing times. The purpose of this research is to find out the learning orientation of Mandarin language Chinese Language Study Program the second year students. This type of research is a type of qualitative research. Researchers want to dig up in-depth information about the orientation of students of the Chinese Language Study Program, State University of Malang, the second year students towards learning Mandarin. The results of this study indicate that second year of students consists of students who have a extrinsic and intrinsic orientations that appear side by side with instrumental and integrative orientations.